2013
DOI: 10.1186/1471-2180-13-42
|View full text |Cite
|
Sign up to set email alerts
|

Global transcriptional responses to the bacteriocin colicin M in Escherichia coli

Abstract: BackgroundBacteriocins are protein antimicrobial agents that are produced by all prokaryotic lineages. Escherichia coli strains frequently produce the bacteriocins known as colicins. One of the most prevalent colicins, colicin M, can kill susceptible cells by hydrolyzing the peptidoglycan lipid II intermediate, which arrests peptidoglycan polymerization steps and provokes cell lysis. Due to the alarming rise in antibiotic resistance and the lack of novel antimicrobial agents, colicin M has recently received re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 81 publications
4
12
0
Order By: Relevance
“…The transcriptional response to bactericidal serum observed in this study was strikingly similar to that reported previously in E. coli treated with ␤-lactam antibiotics and colicin M (48,49). These have a common target in synthesis of peptidoglycan (PG).…”
Section: Discussionsupporting
confidence: 72%
“…The transcriptional response to bactericidal serum observed in this study was strikingly similar to that reported previously in E. coli treated with ␤-lactam antibiotics and colicin M (48,49). These have a common target in synthesis of peptidoglycan (PG).…”
Section: Discussionsupporting
confidence: 72%
“…No phenotypic changes were observed for the multiple creABCD mutants analyzed, but significant differences were observed for the cbrA and cbrBC double mutants. In- terestingly, subinhibitory concentrations of colicin M induce the transcription of genes involved in adaptive responses, including the two-component CreBC system associated with increased resistance to some colicins (45). Recent studies have demonstrated that CbrA, being a nonessential protein, confers high resistance to colicin M and renders cells resistant to osmotic shock in a CreBCdependent manner (46).…”
Section: Resultsmentioning
confidence: 99%
“…We postulate that increased production of EPS-I in these mutants is part of a peptidoglycan stress response. Such a response has not been characterized in rhizobia previously, but in response to peptidoglycan-targeting antibiotics, E. coli and Pseu-domonas aeruginosa increase production of the exopolysaccharides colanic acid and alginate, respectively (75,76). If peptidoglycan stress triggers EPS-I production in S. meliloti, it could explain the EPS-I phenotypes of the cbrA and podJ cell division mutants (53,77).…”
Section: Resultsmentioning
confidence: 97%